Short Communication: The diversity of butterflies (Superfamily Papilionoidea) as a success indicator of tin-mined land revegetation - DINDA WIRANTI; EDDY NURTJAHYA; DAHELMI DAHELMI (Society for Indonesian Biodiversity, 2019)
Abstract. Wiranti D, Nurtjahya E, Dahelmi. 2019. Short Communication: The diversity of butterflies (Superfamily Papilionoidea) as a success indicator of tin-mined land revegetation. Biodiversitas 20: 1923-1928. Some former tin-mining areas in Belitung District have been revegetated. With the increase of vegetation age, the environmental quality changes, and so does the diversity of insects living in the vegetated areas. The objective of this study was to propose the use of butterfly diversity as a success indicator of tin-mined land revegetation. The research was conducted at six locations in Belitung District, consisting of one tin-mined land that had not been revegetated, four revegetated tin-mined lands with different ages of vegetation, namely 1-5 years, 5-10 years, 10-20 years, more than 20 years, and primary forest in Gunung Tajam. The research used the Pollard walk method and specimens were obtained using insect nets. The results showed that the highest diversity of butterflies was recorded in primary forest (31 species), followed by vegetated mined lands with the following ages of vegetation: > 20 years (21 species), 10-20 years (15 species), 5-10 years (14 species ), and 1-5 years (7 species), and the lowest diversity was found in tin-mined land that had not been revegetated (2 species). The Shannon-Wiener diversity index in tin- mined land that had not been revegetated was low, namely 0.56 while in the revegetated tin mined land was medium, i.e., 1.47 – 2.96 and in primary forest was high, i.e., 3.2. The diversity of butterflies in revegetated land increased with the increasing age of vegetation, and the community similarity index between revegetated land and forest also increased with the increasing age of vegetation. Therefore, the diversity of butterflies may be used as a success indicator of revegetation in former tin mining areas.